Kesenjangan Riset dan Tata Kelola Bencana Gunung Semeru: Analisis Tren dan Implikasi Kebijakan - Oscar Radyan Danar; Henri Vannes Christian Son; Dhefara Hersaning Djati (Jurnal Administrasi dan Kebijakan Publik, 2026)
Disaster governance in Indonesia continues to face structural challenges, particularly in integrating scientific knowledge into coherent and adaptive public policy. This study argues that current disaster management remains partial, shaped by technocratic dominance and weak multi-level governance integration. Mount Semeru in East Java is examined as a critical case due to its recurrent eruptions, complex institutional arrangements, and the persistent gap between national policy frameworks and local implementation. Using a Systematic Literature Review (SLR) combined with bibliometric analysis, this study maps research trends, thematic structures, and knowledge gaps in volcanic disaster governance. The findings reveal a strong epistemic bias toward geophysical and technical studies, while critical dimensions such as policy integration, institutional capacity, and community participation remain marginal. This imbalance contributes to a science–policy gap, where available knowledge fails to translate into adaptive and context-sensitive governance. By identifying these gaps, the study contributes to shifting the focus from hazard-centered analysis toward governance-oriented perspectives and provides an evidence base for strengthening disaster policy integration and institutional capacity in volcanic risk management, particularly in the context of Mount Semeru.